Pelesapan Struktur Kalimat Bahasa Iklan Sebagai Inovasi Bahan Ajar Kalimat Majemuk Bahasa IndonesiaSmp Kelas Vii Semester 1 - Rohmah, Meliana Nur; , Drs. Agus Budi Wahyudi, M.Hum (2017)
This descriptive qualitative research aims to (1) describe the form of the language sentence of advertisement before and after dilespakan, (2) describe the element of the ad sentence language function before and after dilesapkan and, (3) to describe the design of teaching materials compound sentence SMP class VII. To achieve that goal, this research uses descriptive research design qualitative study of syntax. The presence of researchers as a key instrument, while the object of research in the form of the function of the elements of the language sentence language in the newspapers and social media. The data in the form of a sentence contained in the ad. Data sourced from newspapers and social media collected memalui methods refer to the technique record. The data were analyzed by using the agih method, the agih method used by researchers to examine the deletion that occurs in the language of advertising and classify in the delegation of subject, predicate, object and description. The results of this study are (1) Solopos newspaper there is a percolation, the occurrence occurs in some functions of sentence elements such as on the subject, predicate, object, and description, as well as a combination of several elements of the sentence, namely a) The sentence form found is 9 whole sentences and 9 sentences are not intact, b) pronunciation predicate there are 9 data, sentence form found that is 4 sentences intact and 5 sentences not intact, c) impediment object there are 6 data, sentence form found 3 sentence Intact and 3 incomplete sentences, d) deletion of information contained 5 data, sentence form found 4 whole sentences and 1 sentence is not intact. (2) The result of this research is in the form of language advertisement by using Solo Pos data source and social media which serve as alternative of innovative teaching material of exposition text material in SMP class VII. (3) In the teaching materials compose new exposition texts arranged on the basis of finding a compound word applied to the exposition text and recasting the new exposition texts based on the expressioned word, such as the teaching material on summarizing exposition texts.